Validation of a Physical Activity and Health Questionnaire for Young People - Lavaho, Sandra Milena Moreno; Rojo, Jorge; Gómez, Jorge Pérez; Devia, Constanza Palomino (Migration Letters, 2024)
The objective was to design and validate a questionnaire that measures the degree of knowledge of young people about the physical activity and health recommendations of the World Health Organization. Methodology: A quantitative, non-experimental, descriptive and cross-sectional study was carried out, for its elaboration a disciplinary team was formed, a pilot test and validation of the questionnaire were formed. Content validity (CVI and Tristan), construct validity (Kolmogorov-Smirnov) and principal component factor analysis, and reliability of internal consistency (Cronbach’s alpha) were determined. Results: the final questionnaire, consisting of 20 items with 2 dimensions physical activity and health, completed the online questionnaire. Factor analysis showed a probable structure of 2 factors, with 41.16% of the total variance, global content validity (CVI=0.79), construct validity, and Cronbach’s alpha reliability (0.71). Kaiser-Meyer.Olkin (KMO=0.72) and Bartlett’s sphericity test (p<0.001) were performed. Conclusions: The questionnaire designed is agile, valid and reliable to measure knowledge about physical activity and health according to the World Health Organization. In this general context, it is especially necessary to know the validity and reliability of the instruments used in the assessment of physical activity, since the existing psychometric instruments and their use for diagnostic purposes offer questionable results. It should be noted that there is no published evidence that records an instrument. Is Cuafys-J a valid tool to measure knowledge about the WHO’s physical activity and health recommendations in young people?